Evaluation of structural epoxy and cyanoacrylate adhesives on jointed 3D printed polymeric materials - Yap, Yee Ling (2020)
In this paper, comparisons of the adhesive strengths of two commercially available adhesives, epoxy and cyanoacrylate, on 3D printed plastic materials, Acrylonitrile Styrene Acrylate (ASA) and Nylon 12 Carbon Fiber (NCF) were carried out. The single lap shear test is used to determine the adhesive properties of the specimens with and without post-curing at elevated temperature. A comparison is made with fully printed, non-bonded specimens to give a relative gauge of the performance of the adhesives. It was found that for ASA and NCF, the adhesive strength for cyanoacrylate (CA) is much higher than that of epoxy. ASA and NCF bonded with CA had average failure load of 1810 kN and 2310 kN, respectively, as compared to those bonded with epoxy which had significantly lower failure load of 470 kN and 860 kN, respectively. It was observed that although heat treatment and surface treatment improve the adhesive strength of epoxy with both adherend materials, the improved adhesive strength of epoxy is still observed to be significantly weaker than that of CA.